Stability of Analytic and Numerical Solutions for Differential Equations with Piecewise Continuous Arguments - Minghui Song; M. Z. Liu (Abstract and Applied Analysis)
In this paper, the asymptotic stability of the analytic and numerical solutions for differential equations with piecewise continuous arguments is investigated by using Lyapunov methods. In particular, the linear equations with variable coefficients are considered. The stability conditions of the analytic solutions of those equations and the numerical solutions of the 𝜃-methods are obtained. Some examples are illustrated.